In vivo misreading by tRNA overdose. - Navarro, F (2000)
Rpb5-H147R is an AT-GC transition replacing CAC(His) by CGC(Arg) at a conserved and critical position of ABC27 (Rpb5p), one of the five common and essential subunits shared by all three eukaryotic RNA polymerases. This mutation is viable at 25 degrees C, but has a lethal phenotype at 34 degrees C. A search for dosage-dependent suppressors identified five distinct clones that all bear a copy of the tRNA(His)GUG gene. Suppression was also observed with a small genomic insert bearing this tRNA gene and no other coding sequences, under conditions where there is a sevenfold increase in the cellular concentration of tRNA(His)GUG. Overexpressing tRNA(Arg)ICG, which normally decodes the suppressed CGC codon, counteracted suppression. Suppression is codon specific because it was abolished when replacing CGC by its synonymous codons CGA, CGU, or AGA, but was not detectably affected by several nucleotide substitutions modifying the surrounding sequence and is thus largely insensitive to the nucleotide context. It is proposed that overexpressing tRNA(His)GUG extends its decoding properties from CAC(His) to the noncognate CGC(Arg) codon through an illegitimate U x G pairing at the middle base of the anticodon. Accordingly, tRNA(His)GUG would compete with tRNA(Arg)ICG for chain elongation and generate a significant level of misreading errors under normal growth conditions.